BELAJAR MENYENANGKAN: PENGGUNAAN QUIZIZZ UNTUK MENINGKATKAN MOTIVASI SISWA KELAS 5 PADA PELAJARAN TIK - Wiyono; Rahmadani, Kurniati; Subroto, Desty (Cakrawala Pedagogik, 2024)
The use of innovative learning media has become the main focus in efforts to increase student interest and motivation in learning at various levels of education. This research aims to investigate the effect of using the Quizizz learning media on the interest and motivation to learn in grade 5 students in Information and Communication Technology (Computer) subjects at SD YPWKS V Cilegon. The research method used was an experiment with a pre-post test design and a randomized control group. The research sample consisted of two randomly selected groups of 5th grade students, totaling 65 students, on July 17 2024. The research results showed that the use of Quizizz learning media significantly increased the interest and motivation to learn in 5th grade students in Information and Communication Technology subjects ( Computer) at YPWKS V Cilegon Elementary School. The experimental group showed a greater increase in interest and motivation to learn compared to the control group. These findings indicate that the integration of Quizizz learning media can be an effective strategy in increasing students' interest and motivation to learn, especially in Information and Communication Technology subjects at the elementary school level. The implication of this research is the importance of technology-based learning approaches in enriching students' learning experiences and improving their academic achievements.